The Salton Sea Proceedings of the Salton Sea Symposium, held in Desert Hot Springs, California, 13–14 January 2000 - Barnum, Douglas A.; Elder, John F.; Stephens, Doyle; Friend, Milton (Springer Netherlands, 2002)
For the first time, an effort to conduct coordinated interdisciplinary research on a vast and complex saline lake has been undertaken for the purposes of providing baseline data to guide restoration project activities. This volume compiles state-of-the-art science for the Salton Sea and will serve as the foundation for the next several generations of scientific inquiry for California's largest lake. The science presented here reveals the Salton Sea to be one of the most productive fisheries in the world, details why the Salton Sea is important to migratory and wintering birds, investigates the microbial world and reports numerous taxa new to science, and documents chemical and physical interactions which make this inland saline lake function. This book is intended for specialists in saline lake research who are interested in all aspects of saline lake ecology
Keywords: Ecology; Freshwater & Marine Ecology; Animal Systematics/Taxonomy/Biogeography; Geochemistry; Aquatic biology